The dynamics of political identity and issue attitudes in adolescence and early adulthood. (April 2017) - Rekker, Roderik; Keijsers, Loes; Branje, Susan; Meeus, Wim
Abstract: This cohort-sequential longitudinal study among 1302 Dutch youths examined the dynamics of political identity (e.g., Democrat or Rightist) and issue attitudes between age 12 and 30. Some theories propose that voters form an identity early in life that subsequently determines attitudes. Other theories contrarily argue that attitudes are a cause of identity. However, research on this controversy has never focused on the crucial phase of adolescence. Results revealed that youths formed an identity consistent with prior attitudes more than vice versa. Highly educated youths most often adjusted their attitudes to their identity, which explained an emerging education gap in identity-attitude consistency. Finally, findings suggested that early cultural attitudes establish an identity that may subsequently determine economic attitudes. Highlights: Adolescents and young adults form a political identity consistent with prior issue attitudes more than vice versa. Low and highly educated voters strongly diverge in identity-attitude consistency during adolescence and early adulthood. Highly educated adolescents and young adults more often adjust their attitudes to their identity than low educated youths. Political identity appears to be rooted in core cultural attitudes that voters acquire during childhood.